Quinoa e amaranto: aspectos gerais, hábito de compra e consumo e cinética de hidratação dos grãos - Schmidt, Davi (2021)
Quinoa (Chenopodium quinoa) and amaranth (Amaranthus spp.) are pseudocereals with elevated nutritional and functional qualities. The first chapter presents a review of the literature on quinoa and amaranth, highlighting their morphological, agronomic, nutritional and socioeconomic aspects. In the second chapter, the objective was to identify the profile of consumers of quinoa and amaranth in addition to observing their consumption habits in relation to these foods. The data was collected through the application of an online questionnaire, which contained questions about the consumer's profile, the knowledge and consumption of quinoa and amaranth, the diversification of food and the preference and choice of packaging. In the third chapter, the objective was to evaluate the hydration kinetics of quinoa and amaranth grains, in order to observe the transfer of water mass to the grains. Tests were carried out at four temperatures (25, 50, 75 and 100 °C), monitoring the mass gain by water absorption and applying the Peleg model to the data obtained. It was concluded that quinoa and amaranth have great potential for composing functional diets, bringing benefits to the health of those who consume them, and that broader dissemination of these foods can contribute to their inclusion in the diet of more and more people.